Problems of State Civil Apparatus Governance Centralistic In Law No. 5 of 2015 Concerning State Civil Apparatus - Ahmad Azharil; Daly Erni (Faculty of Law, Merdeka University Surabaya, Indonesia, 2023)
The existence and role of state civil apparatus in the field of public services has a strategic position if without the role of state civil apparatus,the state's obligation to serve its citizens will not be carried out. The problems faced in the implementation of public services include the organizational management system that has not been maximized, the occurrence of disciplinary violations committed by state civil apparatus, poor performance, poor quality of public services provided, a lot of overlapping state civil apparatus, not maximally provided by the state, and Often there is the implementation of tasks that are not in accordance with their duties and responsibilities. At this time, the election of regional heads is a source of problems for mutations on a large scale, usually the elected regional heads make changes in the form of changing and decreasing positions to changing the workplace of an state civil apparatus. Then how is the governance of the state civil apparatus centralized and how is the merit system in managing the state civil apparatus. The research method used in this study uses qualitative methods, namely a research method by means of interviews, observation, documentation in collecting data, then on the data that has been found a data analysis will be carried out. According to the Indonesia State Civil Apparatus Act Law, the state civil apparatus recruitment system in Indonesia is inappropriate for regional head officials to transfer state civil apparatus for political reasons, based on proximity and others. If the regional head transfers his state civil apparatus without paying attention to the regulatory aspects, then a regional head has violated the law. The implementation of state civil apparatus governance in Indonesia is currently regulated by many rules, so that the legal rules for state civil apparatus governance support strongly. However, in terms of substance there are still many problems. There are so many rules that are not considered by regional head officials in transferring or promoting state civil apparatus.